Creating an Eco‐Friendly Building Coating with Smart Subambient Radiative Cooling. Issue 42 (13th September 2020) - Xue, Xiao; Qiu, Meng; Li, Yanwen; Zhang, Q. M.; Li, Siqi; Yang, Zhuo; Feng, Chi; Zhang, Weidong; Dai, Jian‐Guo; Lei, Dangyuan; Jin, Wei; Xu, Lijin; et al.
Abstract: Subambient daytime radiative cooling (SDRC) provides a promising electricity‐ and cryogen‐free pathway for global energy‐efficiency. However, current SDRC systems require stringent surface designs, which are neither cost‐effective nor eco‐friendly, to selectively emit thermal radiation to outer space and simultaneously maximize solar reflectance. Here, a generic method is developed to upgrade the conventional building‐coating materials with a peculiar self‐adaptive SDRC effect through combining particle scattering, sunlight‐excited fluorescence, and mid‐infrared broadband radiation. It is also theoretically proved that heat exchange with the sky can eliminate the use of resonant microstructures and noble metal mirrors in conventional SDRC, and also leads to enhanced daytime cooling yet suppressed nighttime overcooling. When exposed to direct sunlight, the upgraded coating over an aluminum plate can achieve 6 °C (7 °C on a scale‐model building) below the ambient temperature under a solar intensity of 744 W m −2 (850 W m −2 ), yielding a cooling power of 84.2 W m −2 . The results pave the way for practical large‐scale applications of high‐performance SDRC for human thermal comfort in buildings. Abstract : A waterborne building coating with smart subambient radiative cooling (SSRC) is created based on a new design concept, which combines particle scattering, sunlight‐excited fluorescence, and mid‐infrared broadband radiation. Consequently, conventional building‐coating materials can be engineered at low cost to realize SSRC, facilitating an eco‐friendly solution for widespread applications of the SSRC technology in buildings for improved human comfort.